KONSEP KEBEBASAN BERAGAMA DALAM ISLAM DAN KRISTEN - Wijayanti, Tri Yuliana (Universitas Muhammadiyah Surakarta, 2016)
This research aims to identify and explain matters related to academic problems,namely: first, understand the formulation of religious freedom in the Islamic religion and religiousfreedom in the formulation of the Christian religion. Second, understand the differenceand points alignment of religious freedom contained in Islam and Christianity. This study wasa qualitative research with religious knowledge as the scope of its research and literature as aplace of research (library research). The collected data is then presented descriptively by usingthe approach of sociology of religion. Sources of data in this study were classified into twogroups, namely primary data and secondary data. The data collected by using documentationand tested the validity of test data by applying confirmability (objectivity of research). Thecollected data were then analyzed with a comparative analysis and deductive models. Basedon the analysis, researchers concluded that Islam and Christianity have their own meaning ofreligious freedom. Freedom of religion in Islam and Christians when studied by the method ofcomparative religion, it will show the differences—on the basis of the law of religious freedom,the freedom of religion, and the norms of religious freedom—and side alignment in the sense—the freedom of each individual to embrace religion according to his individual—and embodiedthe goals of religious freedom is to realize the inter religious harmony.Keywords: freedom of religion; Islam; ChristianAbstrak: Penelitian ini bertujuan untuk mengetahui dan menjelaskan hal-hal yang terkaitdengan problem akademik, yaitu: pertama, memahami rumusan kebebasan beragama dalamagama Islam dan rumusan kebebasan beragama dalam agama Kristen. Kedua, memahami letakperbedaan dan poin kesejajaran kebebasan beragama yang terdapat dalam dalam Islam danKristen. Penelitian kualitatif ini dengan ilmu agama sebagai ruang lingkup penelitiannya dankepustakaan sebagai tempat penelitiannya (library research). Data yang didapat kemudiandisajikan secara diskriptif dengan menggunakan pendekatan ilmu sosiologi agama. Sumberdata dalam penelitian ini diklasifikasikan ke dalam dua golongan, yaitu data primer dan datasekunder. Data-data dikumpulkan dengan menggunakan teknik dokumentasi dan diuji validitasdatanya dengan menerapkan uji confirmability (obyektivitas penelitian). Data dianalisisdengan komparatif dan deduktif. Kesimpulan, bahwa agama Islam dan Kristen memilikipemaknaan tersendiri tentang kebebasan beragama. Kebebasan beragama dalam Islam danKristen ketika dikaji dengan metode perbandingan agama, maka akan terlihat sisi perbedaan—yakni pada sisi dasar hukum kebebasan beragama, batas kebebasan beragama, dan norma kebebasanberagama—dan sisi-sisi kesejajaran yakni pada pengertian—kebebasan tiap individuuntuk memeluk agama sesuai dengan keyakinannya masing-masing—dan tujuan dari terwujudkankebebasan beragama yaitu mewujudkan kerukunan antar umat beragama.Kata Kunci: kebebasan beragama; agama Islam; agama Kristen